Dynamic swirl distortion characteristics in S-shaped diffusers using UCNS3D and time-resolved, stereo PIV methods - Piovesan, Tommaso; Migliorini, Matteo; Zachos, Pavlos K.; Tsoutsanis, Panagiotis (American Institute of Aeronautics and Astronautics (AIAA), 2024)
Embedded propulsion systems are key enablers of future aircraft configurations with expected benefits in reduced environmental impact and enhanced performance. Such propulsion systems are typically integrated with convoluted, complex air induction systems whose dynamic distortion characteristics previously found detrimental to the engine’s stability. Therefore, predictive capability for these complex flows is critical for the design of closely coupled engine – intake architectures. A new High-Order Delayed Detached Eddy Simulation (HODDES) is applied in this work to predict dynamic flow distortion within an S-shaped subsonic diffuser. The aim is to assess the ability of a new solver to predict unsteady and extreme distortion events. The HODDES results have been validated with Time-Resolved Stereo PIV (TR-PIV) data. The analysis shows that the HODDES captures the key mean and unsteady flow characteristics, the spectral content and unsteady distortion descriptor behavior across the Aerodynamic Interface Plane (AIP). Although the predicted mean velocity levels, flow field unsteadiness and range of predicted velocities are notably higher than the ones observed at the experiment by at least 40%, it is suggested that this is an artifact of a discrepancy between the axial planes where the CFD and test data were analyzed. The findings of the work suggest that the HODDES is broadly capturing the dynamic flow fields and with some further effort towards the calibration of its RANS models can be further used to study the integration of closely coupled fan system downstream of air induction systems.